Accretion on to strange-matter pulsars - Benvenuto, Omar Gustavo (1994)
We study the effects of the accretion of normal matter on to strange-matter pulsar models. It is assumed that, because of the high strangeness barrier, normal matter is inert in contact with Q α matter. For this reason, normal matter accretion is able to form a thick outer layer with densities far above neutron drip. Accretion can make the superfluid quark-alpha Q α a layer disappear by solidification but, for the same reason, a superfluid neutron layer is formed. The fractional moment of inertia of the latter is large enough to fulfil the vortex-creep glitch model requirements. The high rotational stability of millisecond pulsars is discussed in the framework of the strange-matter hypothesis